Más allá de la estadística: genómica y la construcción genética de la depresión - Delvitto, Ailin; Petino Zappala, María Alejandra; Lavagnino, Nicolás José; Caponi, Sandra (Principia, 2025)
The global increase in the incidence of depression has sparked debates about a potential "epidemic". Within this context, there is academic criticism directed at the current state of psychiatric practice and knowledge, particularly concerning the validity of depression diagnostic criteria. Precision Psychiatry, combined with Disease Genomics, emerges as a potential solution to enhance diagnostic accuracy. Our research involves a methodological and epistemological analysis of the biological bases of depression as framed by Disease Genomics, focusing on the strategies used to study depression and their relationship to the development of diagnostic and treatment technologies. We found a scenario where non-significant associations between genetic variants and depression diagnosis in initial genomic studies were interpreted as methodological failures and challenges in statistical power. Consequently, efforts have aimed to increase statistical power through statistical strategies, conceptualizing depression as a genetically-based condition, albeit simplified and decontextualized. This focus on identifying specific genetic bases is also justified by the goal of developing more precise diagnoses and more effective treatments. Finally, we pose the question of whether these strategies truly aim to clarify the boundaries of diagnosis, heavily criticized for pathologizing "normal" human suffering, or rather to deepen this trend towards a more biologically and genetically oriented understanding of depression.
Gesehen am 09.02.2026